Photocatalytic Pt(IV)‐Coordinated Carbon Dots for Precision Tumor Therapy. Issue 36 (28th October 2022) - Guo, Dongbo; Lei, Josh Haipeng; Rong, Dade; Zhang, Tesen; Zhang, Bohan; Tang, Zikang; Shen, Han‐Ming; Deng, Chu‐Xia; Qu, Songnan
Abstract: Rapid, efficient, and precise cancer therapy is highly desired. Here, this work reports solvothermally synthesized photoactivatable Pt(IV)‐coordinated carbon dots (Pt‐CDs) and their bovine serum albumin (BSA) complex (Pt‐CDs@BSA) as a novel orange light‐triggered anti‐tumor therapeutic agent. The homogeneously distributed Pt(IV) in the Pt‐CDs (Pt: 17.2 wt%) and their carbon cores with significant visible absorption exhibit excellent photocatalytic properties, which not only efficiently releases cytotoxic Pt(II) species but also promotes hydroxy radical generation from water under orange light. When triggered with a 589 nm laser, Pt‐CDs@BSA possesses the ultrastrong cancer cell killing capacities of intracellular Pt(II) species release, hydroxyl radical generation, and acidification, which induce powerful immunogenic cell death. Activation of Pt‐CDs@BSA by a single treatment with a 589 nm laser effectively eliminated the primary tumor and inhibited distant tumor growth and lung metastasis. This study thus presents a new concept for building photoactivatable Pt(IV)‐enriched nanodrug‐based CDs for precision cancer therapy. Abstract : A solvothermally synthesized photoactivatable Pt(IV)‐coordinated carbon dots (Pt‐CDs) and their bovine serum albumin (BSA) complex (Pt‐CDs@BSA) as a novel orange light‐triggered anti‐tumour therapeutic agent with significant visible absorption exhibit excellent photocatalytic properties, which possess ultrastrong cancer cell killing capacities of intracellular cytotoxic Pt(II) species release, hydroxyl radical generation, and acidification, which induce powerful immunogenic cell death (ICD).